2022
DOI: 10.1590/2177-6709.27.1.e2220159.oar
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α levels and presence of SNP-308G/A of TNF-α gene in temporomandibular disorder patients

Abstract: Introduction: Temporomandibular disorder (TMD) refers to a group of conditions that compromise the harmonious movement and function of the temporomandibular joint, masticatory muscles, and associated structures. The etiopathogenesis of TMD is multifactorial but not well-understood, with the role of genetic factors still being unclear. Objective: This review aims to summarize the results of studies that evaluated TNF-α levels and the -308G/A TNF-α polymorphism in TMD patients. This study emphasizes the importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Furthermore, the insertion of removable partial dentures did not prevent CMDs and did not improved oral function. The study by Reissman et al [1] confirmed these statements: the results of their study provided no evidence that replacing missing posterior teeth with removable prostheses reduced the risk of CMD (OR: 0.7). The preservation of a shortened dental arch was not a major risk factor for the development of CMD.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Furthermore, the insertion of removable partial dentures did not prevent CMDs and did not improved oral function. The study by Reissman et al [1] confirmed these statements: the results of their study provided no evidence that replacing missing posterior teeth with removable prostheses reduced the risk of CMD (OR: 0.7). The preservation of a shortened dental arch was not a major risk factor for the development of CMD.…”
Section: Discussionmentioning
confidence: 93%
“…Ten articles met the eligibility criteria and were included in the systematic review. [1,4,[6][7][8][9][10][11][12][13] A total of 10 publications were included in our study:…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations